2021
DOI: 10.1111/apt.16632
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for hepatocellular carcinoma occurrence in patients with hepatitis C in the era of direct‐acting anti‐virals

Abstract: Background: Several factors associated with hepatocellular carcinoma (HCC) occurrence after sustained virological response (SVR) in patients with hepatitis C have been reported. However, few validation studies have been performed in the era of direct-acting anti-virals (DAAs). Aims:To develop a prediction model for HCC occurrence after DAA-mediated SVR and validate its usefulness. Methods:We analysed 2209 patients with SVR and without a history of HCC who initiated DAA treatment at 24 Japanese hospitals. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
2
27
1
Order By: Relevance
“…We previously reported that AFP levels at SVR was an independent predictor for HCC incidence in patients treated with DAA, including patients with and without advanced liver fibrosis. 14 The AFP level at SVR could be a surrogate marker of HCC incidence, even in patients without advanced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that AFP levels at SVR was an independent predictor for HCC incidence in patients treated with DAA, including patients with and without advanced liver fibrosis. 14 The AFP level at SVR could be a surrogate marker of HCC incidence, even in patients without advanced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These cut-off values were set based on previous reports. 14,27,28 We undertook statistical analyses using SPSS version 24.0 (IBM), and considered a two-tailed p-value less than 0.05 to be statistically significant in all analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…All the additional data required for such model refinement is available and we are currently investigating this possibility. Our analysis suggests the aMAP score possesses all the qualities required for practical risk stratification in HCC surveillance [31].…”
Section: Discussionmentioning
confidence: 87%
“…Another study, from Tani et al, used a simple scoring system based on age of HCV patients and AFP level after DAA treatment to select patients with a high risk of HCC development [61]. Finally, a prediction model combining body mass index, FIB-4, and albumin and AFP level at sustained response time points was recently proposed as an efficient surveillance strategy for HCC occurrence after DAA treatment [62].…”
Section: Predictive Models and Scoresmentioning
confidence: 99%